Trends in HIV prevalence by self-report among MSM diagnosed and reported with gonorrhea in six United States jurisdictions from 2010 to 2019. (1st December 2021) - Stenger, Mark Richard; Pathela, Preeti; Schumacher, Christina; Burghardt, Nicole; Amiya, Rachel; Madera, Robbie; Nguyen, Trang Q.; Torrone, Elizabeth
Abstract : Supplemental Digital Content is available in the text Abstract : Background: HIV co-infection among persons diagnosed with gonorrhea is not well characterized. Trends in HIV prevalence among persons diagnosed with gonorrhea may have significant implications for HIV prevention interventions, especially for MSM. MSM are increasingly and disproportionately represented among incident gonorrhea cases reported in a multistate sentinel surveillance network. Using data from this network, we estimated HIV prevalence among MSM by self-report and explored trends in co-infection by key demographics. Design: Observational study using enhanced surveillance data. Methods: Six geographically diverse jurisdictions in the STD Surveillance Network (SSuN) 2010–2019 randomly sampled laboratory-confirmed gonorrhea cases. Enhanced investigations on sampled cases included patient interviews eliciting demographic, behavioral and HIV testing history. These data were weighted to adjust for study design and nonresponse to estimate trends in HIV prevalence. Results: Of 653 522 reported cases, 28 979 were sampled and investigated. The proportion of cases reporting living with diagnosed HIV at the time of their gonorrhea diagnosis increased 61% across the study period from 6.6% in 2010 to 10.8% in 2019. The observed increase in HIV prevalence is concurrent with an increase in the proportion of gonorrhea cases attributable to MSM. HIV prevalence among MSM decreased in two jurisdictions and increasing trends were observed among non-Hispanic Black and Hispanic MSM. HIV prevalence decreased among non-Hispanic white MSM, MSM under 20 and those 40 years of age or older. Conclusion: Diagnosis with gonorrhea, especially among MSM, should be a sentinel event triggering screening for HIV, referral to high-impact HIV prevention interventions or to HIV primary care.